Development and calibration of an electrolytic cell for ion determination in a soil solution - Pereira, Omar Cleo Neves; Bertonha, Altair; Freitas, Paulo Sergio Lourenço de; Silvano, Caroline (Acta Scientiarum. Technology, 2015)
An electrolytic cell was developed to monitor soil modifications after crop fertigation with wastewaters from agroindustrial plants. The device was first calibrated with different levels of potassium chloride dissolved in aqueous solutions at various temperatures. NernstÂ´s model was used to fit the voltage indicated from the electrolytic cell versus the ionic activity of the potassium from the aqueous solutions of electrical conductivity and known ionic concentrations and the diluted wastewater samples. The equipment accurately indicated the tensions after appropriated correction of the electrical current and the temperature. The device estimated with accuracy the ionic coefficient of activity, the concentration of the potassium chloride and the concentration of the ion K dissolved in the agro-industrial wastewater. Â